Advancing reservoir operations modelling in SWAT to reduce socio-ecological tradeoffs. (November 2022) - Jordan, Sarah; Quinn, Julianne; Zaniolo, Marta; Giuliani, Matteo; Castelletti, Andrea
Abstract: The Soil & Water Assessment Tool (SWAT) is a useful model for evaluating socio-ecological tradeoffs and analyzing coupled natural-human system dynamics in agricultural watersheds. However, reservoir operating options in SWAT are limited. This study advances the representation of reservoir operations in SWAT by adding an option for closed-loop, multi-reservoir operating policies that can be optimized using Evolutionary Multi-Objective Direct Policy Search. This enables water managers to evaluate the tradeoffs across more coordinated reservoir operations in SWAT while capitalizing on the model's ability to physically simulate hydrological processes better than traditional reservoir simulation models. Comparing our advanced reservoir operations with SWAT's existing operating options in the Omo River basin of Ethiopia, we find a wider range of policies for managing conflicting stakeholder objectives that better compromise across them and are more robust to climate change. These advances to SWAT's reservoir module show promise for informing integrated water resources management. Highlights: We integrate coordinated, closed-loop reservoir operations into the Soil & Water Assessment Tool. This allows water managers to evaluate tradeoffs of smarter water management options. It also improves the modeling of hydrologic impacts in traditional reservoir models.